Internationalization of agro-food trade in the Visegrad Group countries after their entering into the European Union - Wiśniewska, Joanna (Zeszyty Naukowe SGGW w Warszawie - Problemy Rolnictwa Światowego, 2010)
The foreign trade performance in agro-food sector in the Central European Countries for the period of 2004-2007 has been evaluated. The main exports and imports measures, comparative advantages, specialization as well as market shares and competitiveness have been analyzed. After entering into the European Union by the Central European Countries, the importance of foreign trade in agro-food sector has increased, an intra-branch trade has been intensified and its structure has changed. The comparative position of these countries in the trade has been created by rising comparative advantages of some sections and lowering of the others. The foreign trade turnover has risen and the agro-food trade has been internationalized.